The Habsburg Monarchy 1809-1918 : - Taylor, Alan J. P. (Hamish Hamilton, 1964)
This is the only history, in any language, of the Habsburg Monarchy from the end of the Holy Roman Empire in 1806 until its own dissolution in 1918. It begins with Metternich and ends with Masaryk and the national revolutions. Its theme is the attempt of the Habsburg Emperors and their servants to maintain a great Imperial organisation 'above the nationalities,' which would give central Curope peace and stability; and it analyses the intellectual and social forces, born in the nineteenth century, which brought this attempt to failure.